MAXIMIZING STUDENTS ENGLISH ABILITY TROUGH FACEBOOK - Siti Mafulah (Fakultas Bahasa dan Sastra Universitas Kanjuruhan Malang, 2016)
The development of social media recently in this era is really attractive to be discussed. Almost all students use their mobile phone to access it. So that why we as teacher cannot use this brilliant tool in learning English. Qodriani (2013) said that Facebook is not just a great way for people to find old friend or know about what happening recently but it is also an incredible learning media that can support teaching and learning activity. Attractive media makes learning enjoyable. The design used in this research was descriptive design with 12 students as participants. This research focuses on the English learning through Facebook. How Facebook used in English language class, how students’ perspective of using Facebook in learning English and how Facebook maximize their English will be described in this paper. This activity offers students in learning English and makes enjoyable learning. Moreover students can write and share what they have done or something happened to them without any worrying of making mistake.